Influence of year and soil type on the yield of different maize hybrids - Rajičić Vera; Stojiljković Jelena; Đurić Nenad; Tupajić Ivan; Šević Biljana; Perišić Vesna; Terzić Dragan (Acta Agriculturae Serbica)
During the three-year field trials (2017, 2018 and 2019), 9 maize hybrids of different FAO maturity groups (400-600) were tested. The experiment was set up in three locations - three types of soil, in the Jablanica district, to recommend hybrids for the studied area based on the yield obtained, depending on soil type and the year of cultivation. During the three-year research, the hybrids achieved the highest average yields in 2018, when the amount and distribution of precipitation were most favourable, while the lowest average yield was obtained in 2017, when the amount of rainfall was insufficient during critical development stages. The highest average yields were produced on an alluvium soil, in the area of Leskovac (12.418 t ha-1), and the lowest on parapodzol, in the village of Orašje (8.672 t ha-1). The highest average grain yields in 2017, 2018 and 2019 were achieved by the hybrids ZP 560 (12.820 t ha-1), ZP 606 (15.569 t ha-1) and ZP 560 (14.863 t ha-1), respectively. The higher yields in 2018 can be attributed to higher amounts and a more favourable distribution of precipitation during the growing season than under the agroclimatic conditions in 2017 and 2019.